2019
DOI: 10.1029/2019gl082746
|View full text |Cite
|
Sign up to set email alerts
|

Joint Inversion of Rayleigh Wave Phase Velocity, Particle Motion, and Teleseismic Body Wave Data for Sedimentary Structures

Abstract: Mapping seismic structures of sedimentary basins is of great importance to better evaluate energy resources and seismic hazards. In this study, we develop a joint Bayesian Monte Carlo nonlinear inversion method that utilizes the complementary nature of Rayleigh wave phase velocity, Rayleigh wave particle motion, and teleseismic P wave in responding to sedimentary structures. Synthetic tests demonstrate that our joint inversion can retrieve the input sedimentary models better than inversions with surface or bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…Yang and Niu (2019) studied sedimentary structure of basins in China from frequency‐dependent P ‐wave particle motion. Li et al (2019) successfully isolated the Moho P ‐to‐ S conversion from sediment reverberations with a wavefield‐downward‐continuation technique. They reported a joint inversion that can retrieve the input sedimentary models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang and Niu (2019) studied sedimentary structure of basins in China from frequency‐dependent P ‐wave particle motion. Li et al (2019) successfully isolated the Moho P ‐to‐ S conversion from sediment reverberations with a wavefield‐downward‐continuation technique. They reported a joint inversion that can retrieve the input sedimentary models.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study investigated sedimentary structure of basins in China from frequency dependent P ‐wave particle motion (Yang & Niu, 2019). Li et al (2019) reported a joint inversion of Rayleigh wave phase velocity, particle motion, and teleseismic body wave data for sedimentary structures.…”
Section: Introductionmentioning
confidence: 99%
“…where V obs (t) and H obs (t) represent observed vertical and radial waveforms of P and converted S wave recorded at a given station. Because the Green's functions of the shallow structure (h syn (t,m) and v syn (t,m)) are almost independent from epicentral distances (Li et al, 2019) in the distance range of 30°-90° and the convolution operator is linear, we stack the recorded teleseismic waveforms from different teleseismic events by aligning waveforms according to their maximum vertical amplitude in order to suppress the random noise and to reduce the number of event waveforms to be fitted. Before stacking, for each event, the vertical and radial records are first normalized by the maximum amplitude of the vertical components and the negative polarity is reverse to positive polarity.…”
Section: 1029/2020jb019998mentioning
confidence: 99%
“…A recent study by Li et al. (2019) demonstrates that jointly inverting teleseismic P‐coda waveforms, Rayleigh wave phase velocity and ellipticity can better constrain velocities and velocity discontinuities of sedimentary basins. In this study, we adopt the method developed by Li et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation